Exploration and Practice of Carbon Sequestration Realized by CO2 Waterless fracturing. (February 2019) - Siwei, Meng; He, Liu; Qinghai, Yang
Abstract: Carbon sequestration is an important measure to reduce greenhouse gas emissions. This paper introduces a new method of carbon sequestration using CO2 waterless fracturing technology. Based on the supporting technology system with independent intellectual property rights, waterless fracturing field tests were carried out on 19 wells in Jilin oilfield. The on-site monitoring data shows that CO2 stays in a supercritical state for a long time in the process of waterless fracturing, soaking and flowback, which is favourable for carbon sequestration. The geological model of H87 test area was established to simulate and evaluate CO2 recovery after fracturing. The results show that the storage ratio of CO2 waterless fracturing is 76.46%. Meanwhile, the production after waterless fracturing is 2.4 times that after water-based fracturing with the same scale, and the average single well operation saves 1512 m 3 water. It can be seen that CO2 waterless fracturing is a new type of carbon sequestration technology with high storage efficiency, good stimulation effect, significantly reduction of water consumption during oil and gas reservoir development and has broad market prospects.